Translation and cross-cultural adaptation of the Brazilian version of the Boston Residue and Clearance Scale (BR-BRACS) - Scaranelo, Giulia Beatriz Pozena [UNESP]; Onofri, Suely Mayumi Motonaga [UNESP]; Araújo Pernambuco, Leandro de; Silva, Roberta Gonçalves da [UNESP] (FapUNIFESP (SciELO), 2025)
PURPOSE: This study aimed to translate and cross-culturally adapt The Boston Residue and Clearance Scale (BR-BRACS) into Brazilian Portuguese and validate the image selection content for the scale. METHODS: The project was approved by the Institution's Ethics Committee under number 67715717.6.0000.5406. The process involved translating the scale into the target language, synthesizing the translations, and back-translating it into the original language. A literature review was conducted to define the concept of pharyngeal residue and ensure the content validity of the images representing the scale. Then, 50 fiberoptic endoscopic evaluations of swallowing were analyzed and submitted to three judges for visual-perceptual evaluation. Agreement among the judges was analyzed using Fleiss' Kappa test with a 95% confidence interval. RESULTS: Discrepancies in lexical and syntactic contexts were identified during translation and resolved through a consensus among translators and authors. The back-translated versions were equivalent to the original. The images proposed for the scale showed near-perfect agreement among the judges. CONCLUSION: The translation, cross-cultural adaptation, and selection of images for visual-perceptual evaluation of pharyngeal residue in the BR-BRACS were completed with evidence of content validity.